Migration and global health - Becher, Heiko; Winkler, Volker; Zeeb, Hajo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book attests to the ample research needs and opportunities around migration and health, with a focus on recent as well as earlier migration to Europe. It sheds light on several issues ranging from non-communicable disease epidemiology and health services utilization to aspects of quality of life, and of some methodological challenges